Rabana-Merquly: a fortress in the kingdom of Adiabene in the Zagros Mountains - Brown, Michael; Raheem, Kamal Rasheed; Abdullah, Hashim Hama (Antiquity, 2022)
The mountain fortress of Rabana-Merquly was a major regional centre of the Parthian period (first century BC) in the Zagros Mountains of Iraqi Kurdistan. The iconography of two rock-reliefs that show an unnamed ruler suggests an association with the vassal kingdom of Adiabene. The exceptional preservation of the fortress's stone walls, undamaged by later agriculture in this highland location, provides an almost complete example of a large, fortified site with two main intramural settlements. Through its ability to control the surrounding landscape, Rabana-Merquly highlights the role of client states on the peripheries of the Parthian and Roman Empires and illuminates the practicalities of territorial control by state authorities in hinterland regions.